The relationship of HbA1c levels with creatinin levels in diabetes mellitus type 2 patients - Putri Nur Cahyani; Atik Martsiningsih; Budi Setiawan (PUINOVAKESMAS, 2020)
Background: People with Type 2 Diabetes Mellitus in Indonesia continue to increase in prevalence. Understanding of complications due to this disease, one of which is diabetic nephropathy or damage to kidney nephrons. Objective: To determine the relationship between HbA1c levels and creatinine levels in patients with Type 2 Diabetes Mellitus. Method: This study was an observational experiment using a cross sectional approach based on secondary data. The research was carried out in February to April 2020. The population of this research study is a member of Prolanis (Chronic Disease Management Advanced Program) in Gamping 1 Puskesmas Sleman Yogyakarta. Sample with 24 patients. Analysis of data using the Spearman’s test. Results: From the results of the normality test using the Shapiro Wilk test data obtained were not normally distributed so that continued with the Spearman rank test obtained r of -0.006 and p values with sig. (2-tailed) of 0.961 or> 0.05 (H0 received). This means that there is no relationship between HbA1c levels and blood creatinine levels in patients with type 2 DM. Conclusion: There is no relationship between HbA1c levels and creatinine levels in patients with Type 2 Diabetes Mellitus.